The Work of Informal Environment in Language Learning - Wildona Zumam; Mohammad Amiruddin; Nur Syakherul Habibi (LPPM Universitas Bumigora Mataram, 2023)
This study examines the work of informal environment in language learning. This study is an ex post facto research, employing quantitative approach. The students at English Department of Madura University are as parts of population in the current research. A sample is decided by using proportional stratified random sampling technique. The data are analyzed by simple regression technique. The result of the study shows that the work of informal environment in language learning is not particularly high, 0.43 (43%). The informal environment operates on students’ proficiency level in English. It enriches the students’ input to communicate in English as well as makes the input of students becoming intake. It implies that the teachers and members of academic society should assist students with natural communication in order to meaningful input for the students.